Análisis y elaboración de una base de datos realizada según el censo de equipos electrónicos para uso médico del hospital del IESS Dr. Teodoro Maldonado Carbo - Cruz Obando, Diego (2009)
This topic has two main objectives: The first objective is to realize a poll to the Administrator and the Maintenance Manager of the Hospital of IESS “Dr. Teodoro Maldonado Carbo” and the second objective is to develop a database of the hospital equipment. This topic consists in two parts. The first one, consist of a poll realized for the directives of the Hospital of IESS “Dr. Teodoro Maldonado Carbo”, to know about the level of service offered to the affiliates, which takes as reference standards, codes and policies in the areas of electrical, mechanical, environmental, biological, radioactive and electromagnetic safety. The second part is based in a poll of electronic equipment for medical use in the same hospital, with the aim to recognize the equipment level of different areas and the services it can provide to the community. This poll is also used to determine the causes for which, electronic equipment for medical use, are damaged.